2010
DOI: 10.1158/1055-9965.epi-09-1180
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: Differences in HPV Knowledge between Haitian and African American Women

Abstract: Background: Historically, all black persons, regardless of ancestry or country of origin, have been categorized as one group for cancer research and control efforts. This practice likely masks variability in exposure to determinants of disease, as well as in risk of cancer incidence and mortality. The current study examines potential differences in knowledge of human papilloma virus (HPV) between Haitian women living in Little Haiti, Miami, Florida, and a national sample of predominately African American women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 9 publications
(6 reference statements)
6
32
0
Order By: Relevance
“…Based on data from this study, it seems that providers may need to deliver targeted messages to specific ethnic groups. Strategies that incorporate ethnic diversity within messaging are likely to be more effective than 'one-sizefits-all' approaches (Kobetz et al, 2010). Based on our findings, messages targeting African Americans may need to focus on vaccine safety, whereas messages targeting Haitians should focus on the role of parents' in their daughters' vaccination against HPV, and the appropriate time to vaccinate their daughters.…”
Section: Policy Implicationsmentioning
confidence: 87%
See 2 more Smart Citations
“…Based on data from this study, it seems that providers may need to deliver targeted messages to specific ethnic groups. Strategies that incorporate ethnic diversity within messaging are likely to be more effective than 'one-sizefits-all' approaches (Kobetz et al, 2010). Based on our findings, messages targeting African Americans may need to focus on vaccine safety, whereas messages targeting Haitians should focus on the role of parents' in their daughters' vaccination against HPV, and the appropriate time to vaccinate their daughters.…”
Section: Policy Implicationsmentioning
confidence: 87%
“…Because most existing research in this area has been conducted without differentiating ethnic groups that belong to the same race (Constantine & Jerman, 2007;Dinh et al, 2007;Noel et al, 2007), addressing barriers specific to subgroups of populations who self-identify as "Black" may help to achieve high penetrance of HPV vaccination in minority adolescents (Kobetz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Much of the research has been conducted with Haitian immigrants in the U.S. Studies have shown that Haitian immigrants have varying levels of HPV and HPV vaccine awareness. 1012 HPV awareness is a necessary antecedent of behavior change, 1315 according to several leading stage theories of health behavior. 16–18 Given the dearth of information on HPV awareness in Haiti, we sought to examine levels of HPV awareness and predictors of HPV awareness among healthcare-seeking adults in Port-au-Prince and Léogâne, Haiti.…”
Section: Introductionmentioning
confidence: 99%
“…However, as cultures are never static, it is important to continuously examine how sociohistorical and contextual experiences shape various health outcomes (Castro & Farmer, 2005; Stephens et al, 2012). For example, Haitian communities in the United States have been described as transnational because their cultural beliefs are negotiated via an American and Haitian lens of health (Kobetz et al, 2010). For this reason, it is important to consider how recently immigrated Haitian mothers negotiate various health afflictions and concerns through their own cultural values and current experiences within American contexts.…”
mentioning
confidence: 99%